2010
DOI: 10.1007/s12028-010-9380-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Continuous EEG Monitoring on Clinical Management in Critically Ill Children

Abstract: Background Continuous EEG (cEEG) monitoring is being used with increasing frequency in critically ill patients, most often to detect non-convulsive seizures. While cEEG is non-invasive and feasible in the critical care setting, it is also expensive and labor intensive, and there has been little study of its impact on clinical care. We aimed to determine prospectively the impact of cEEG on clinical management in critically ill children. Methods Critically ill children (non-neonates) with acute encephalopathy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 35 publications
1
50
2
1
Order By: Relevance
“…Seizures have been associated with worse outcome in critically ill adults [23][24][25] and neonates 15,26 -29 and seizure detection impacts anticonvulsant use in children 30 and adults. 31 While plausible mechanisms by which electrographic seizures may lead to brain injury have been described, 32,33 further study is needed to determine whether identification and treatment of NCS and NCSE improves outcome.…”
Section: Results Subject and Enrollment Characteristicsmentioning
confidence: 99%
“…Seizures have been associated with worse outcome in critically ill adults [23][24][25] and neonates 15,26 -29 and seizure detection impacts anticonvulsant use in children 30 and adults. 31 While plausible mechanisms by which electrographic seizures may lead to brain injury have been described, 32,33 further study is needed to determine whether identification and treatment of NCS and NCSE improves outcome.…”
Section: Results Subject and Enrollment Characteristicsmentioning
confidence: 99%
“…Neurol Clin Pract 2017;7:15-25 C ontinuous EEG monitoring (cEEG) in acutely hospitalized patients has increased dramatically throughout the last decade. [1][2][3][4][5][6] cEEG has been particularly helpful in acutely ill patients at risk for nonconvulsive seizures, 4,7,8 and has been reported to contribute to reduced inpatient mortality without additional charges to hospital stay. 9 In addition, cEEG is increasingly used to detect cerebral ischemia in patients at high risk, 5,[9][10][11] with ischemia monitoring protocols often involving monitoring at-risk patients for as long as 10 or more days.…”
Section: Introductionmentioning
confidence: 99%
“…Data obtained from CEEG reportedly affect clinical management in 59% of monitored children, most often by affecting anticonvulsant utilization. 15 Several studies have reported an association between electrographic seizures or status epilepticus and worse outcome, 11,12,16,17 occurring independently of potential confounders related to acute etiology and critical illness severity.…”
mentioning
confidence: 99%
“…26 Similarly, observational studies have reported that CEEG results in anticonvulsant medication changes in about half of critically ill children and adults who undergo CEEG. 15,27 A number of single-center studies have demonstrated an association between electrographic seizures or electrographic status epilepticus and worse outcome in critically ill children. 11,12,14,16,17,28 Our data also indicate that electrographic status epilepticus was associated with higher mortality, even after adjusting for the neurologic diagnosis category and initial EEG background category.…”
mentioning
confidence: 99%